Saccharomyces boulardii Strain CNCM I-745 Modifies the Mononuclear Phagocytes Response in the Small Intestine of Mice Following Salmonella Typhimurium Infection - Ibáñez, Lidia; Pontier-Bres, Rodolphe; Larbret, Frederic; Rekima, Akila; Verhasselt, Valérie; Blin-Wakkach, Claudine; Czerucka, Dorota (Frontiers in Immunology, 2019)
Intestinal mononuclear phagocytes (MPs) comprise dendritic cells (DCs) and macrophages (Mφs) that play different roles in response to Salmonella infection. After phagocytosis, DCs expressing CD103 transport Salmonella from the intestinal tract to the mesenteric lymph nodes (MLN) and induce adaptive immune responses whereas resident Mφs expressing CX3CR1 capture bacteria in the lumen and reside in the lamina propria (LP) where they induce a local immune response. CX3CR1+ Mφs are generated from Ly6Chi monocytes that enter the colonic mucosa and differentiate locally. We previously demonstrated that the probiotic yeast Saccharomyces boulardii CNCM I-745 (S.b) prevents infection by Salmonella enterica serovar Typhimurium (ST), decreases ST translocation to the peripheral organs and modifies the pro-and anti-inflammatory cytokine profiles in the gut. In the present study, we investigated the effect of S.b on the migratory CD103+ DCs and the resident CX3CR1+ Mφs. MPs were isolated from the LP of streptomycin-treated mice infected by ST with or without S.b treatment before or during the infection. In S.b-pretreated mice, we observed a decrease of the CD103+ DCs in the LP that was associated with the drop of ST recovery from MLN. Interestingly, S.b induced an infiltration of LP by classical Ly6Chi monocytes, and S.b modified the monocyte -Mφ maturation process in ST-infected mice. Our results showed that S.b treatment induced the expansion of Ly6Chi monocytes in the blood as well as in the bone marrow (BM) of mice, thus contributing to the Mφ replenishment in LP from blood monocytes. In vitro experiments conducted on BM cells confirmed that S.b induced the expansion of CX3CR1+ Mφs and concomitantly ST phagocytosis. Altogether, these data demonstrate that Saccharomyces boulardii CNCM I-745 modulates the innate immune response. Although here, we cannot explicitly delineate direct effects on ST from innate immunity, S. b-amplified innate immunity correlated with partial protection from ST infection. This study shows that S.b can induce the expansion of classical monocytes that are precursors of resident Mφs in the LP.